Diseño de un sistema de gestión por procesos para mejorar la gestión operativa de la empresa Inversiones Alto Chicama E.I.R.L. - Cruzado Bravo, Jheny Lady (2019)
The purpose of this work was to improve the operational management of Inversiones Alto Chicama E.I.R.L., through the process management system. The research design is experimental; The variables considered were the process management system and the operational management of Inversiones Alto Chicama E.I.R.L. From the diagnosis that has been prepared, an analysis of the results was presented in order to corroborate with quantitative data, the evidence presented and the improvement achieved with the process management system; improving the current existing situation through the standardization of best practices that ensure compliance with the standards required by customers. The implementation proposal was designed and implemented, containing the necessary elements to control the processes that are developed in the company, guaranteeing that the services and products are provided in a consistent manner and according to the expectations of the client. The conclusion being, after having carried out the research study, that the process management system improves the operational management of the company Inversiones Alto Chicama EIRL, being reflected the improvement in the increase of the operational management indicators being the initial index of said indicators of 51% going to 83%, obtaining a favorable margin of 32%.